The NLRP3 Inflammasome as a Novel Player of the Intercellular Crosstalk in Metabolic Disorders. (13th June 2013) - Benetti, Elisa; Chiazza, Fausto; Patel, Nimesh S. A.; Collino, Massimo
Abstract : The combination of obesity and type 2 diabetes is a serious health problem, which is projected to afflict 300 million people worldwide by 2020. Both clinical and translational laboratory studies have demonstrated that chronic inflammation is associated with obesity and obesity-related conditions such as insulin resistance. However, the precise etiopathogenetic mechanisms linking obesity to diabetes remain to be elucidated, and the pathways that mediate this phenomenon are not fully characterized. One of the most recently identified signaling pathways, whose activation seems to affect many metabolic disorders, is the "inflammasome, " a multiprotein complex composed of NLRP3 (nucleotide-binding domain and leucine-rich repeat protein 3), ASC (apoptosis-associated speck-like protein containing a CARD), and procaspase-1. NLRP3 inflammasome activation leads to the processing and secretion of the proinflammatory cytokines interleukin- (IL-) 1 β and IL-18. The goal of this paper is to review new insights on the effects of the NLRP3 inflammasome activation in the complex mechanisms of crosstalk between different organs, for a better understanding of the role of chronic inflammation in metabolic disease pathogenesis. We will provide here a perspective on the current research on NLRP3 inflammasome, which may represent an innovative therapeutic target to reverse the detrimental metabolic consequences of the metabolic inflammation.